Chemical Immunology and Allergy 2005
DOI: 10.1159/000087640
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor Expression by Mast Cells

Abstract: There is a growing interest in the role of chemokines and their receptors in the determination of mast cell tissue localization and how chemokines regulate mast cell function. At least nine chemokine receptors (CXCR1, CXCR2, CXCR3, CXCR4, CX3CR1, CCR1, CCR3, CCR4 and CCR5) have been described to be expressed by human mast cells of different origins. Seven chemokines (CXCL1, CXCL5, CXCL8, CXCL14, CX3CL1, CCL5 and CCL11) have been shown to act on some of these receptors and to induce mast cell migration. Mast ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 30 publications
2
73
0
Order By: Relevance
“…In contrast, ␣1-, ␣2-, and ␣4-laminins were inactive under all the conditions tested. Our observation that cellular responses were enhanced by the physiological stimuli C3a, SCF, and SDF-1␣ was consistent with the reported MC expression of the receptors C3aR, c-kit, and CXCR4 (16,19,34,35). These receptors may regulate the function of laminin-binding integrins.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, ␣1-, ␣2-, and ␣4-laminins were inactive under all the conditions tested. Our observation that cellular responses were enhanced by the physiological stimuli C3a, SCF, and SDF-1␣ was consistent with the reported MC expression of the receptors C3aR, c-kit, and CXCR4 (16,19,34,35). These receptors may regulate the function of laminin-binding integrins.…”
Section: Discussionsupporting
confidence: 90%
“…In light of our observation that mature MC (i) express high levels of CD34 (24,52), (ii) are well known sources of MMP2 and MMP9 (53,54), and (iii) express CCR1 and chemotax in response to CCL9 (reviewed in ref. 55), it is likely that these iMC in fact represent mature MC, degranulated MC, or MCp. This notion is further strengthened by reports that, in human, iMC lack CD34 (6), because we previously have shown that, although the human Cd34 gene is expressed in trafficking MCp, it is shut off as they differentiate into mature MC in the periphery (reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the increased mast cell numbers may be that the survival of resting and activated mast cells is enhanced due to survival gene expression or other mechanisms [148,210] and/or mast cells and their hematopoietic progenitors are recruited from the circulation. For example, mast cells express at least nine chemokine receptors [83] and SCF, TGF-, RANTES and stromal cellderived factor-1 have eYciently induced migration of human mast cells in vitro and therefore they are potent candidates for chemoattraction of mast cells to the tissue site [82,132,139]. In addition to SCF, several other factors have been reported to modulate human mast cell development or survival in vitro, such as IL-3 to IL-6 [213], IL-9 [112], thrombopoietin [158], nerve growth factor [89], and endothelial cells [118].…”
Section: Regulation Of Mast Cell Number and Activity In The Psoriaticmentioning
confidence: 99%
“…Newly synthesized mediators include prostaglandin D 2 , leukotriene C 4 and varying amounts of other lipid-derived mediators. In addition, mast cells can be induced to de novo synthesis of a range of cytokines, chemokines, growth factors, and cell membrane molecules, such as chemokine receptors, receptor ligands, toll-like receptors, MHC class II molecules and co-stimulatory molecules, all of which are crucial in inducing an immune and inXammatory reaction [29,46,83,160].…”
Section: Introductionmentioning
confidence: 99%